Alginate/chitosan-based hydrogel loaded with gene vectors to deliver polydeoxyribonucleotide for effective wound healing. (9th July 2021) - Jing, Xiaodong; Sun, Yanzhen; Liu, Yang; Ma, Xiaoli; Hu, Hao
Abstract : The prepared polydeoxyribonucleotide (PDRN)-loaded alginate/chitosan-based hydrogel as a "nanocomposite smart material" combines the advantages of gene vectors and hydrogels and promotes the wound healing process. Abstract : Timely and effective wound treatment is of great significance in acute bleeding caused by accidents and chronic wounds such as diabetic foot ulcers, venous leg ulcers, pressure sores. A hydrogel as wound dressing can provide a suitable microenvironment for wound healing and prevent bacteria and dust from reaching the wound. The loading of therapeutic factors in the hydrogel has been proved to accelerate wound healing. Polydeoxyribonucleotide (PDRN), as a series of nucleic acid fragments extracted from salmon, has the functions of improving angiogenesis, promoting cell activity, increasing collagen synthesis, and developing the anti-inflammatory response. These effects have positive implications for wound healing. But naked PDRN is difficult to take up by cells. Inspired by gene vectors, we prepared a PDRN-loaded CaCO3 nanoparticle (PCNP) to improve the delivery efficiency of PDRN. PCNPs were encapsulated in an alginate/chitosan-based hydrogel (Gel@PCNPs). The prepared hydrogel has plasticity and is suitable for various irregular wounds. The released gene carrier, PCNP, can be effectively taken up by skin fibroblasts. Under the action of PDRN, the wound healing rate has been confirmed to be significantly accelerated. We believe that this polysaccharide-based hydrogel loaded with PDRN vectors is a promising wound dressing.